Bovine milk and milk protein– promotor or inhibitor of bacterial biofilm formation at the tooth surface? - A. Kensche; C. Pohl; S. Basche; A. Dürasch; T. Henle; M. Hannig; C. Hannig (BMC Oral Health)
Abstract Background The present study aimed to investigate if mouthrinses with different types of bovine milk or milk protein isolates influence the initial bacterial colonization of the tooth surface. Methods From 8 subjects, different biofilm samples were collected in situ on bovine enamel slabs: after 3 min of pellicle formation, mouthrinses with homogenized UHT-milk (0.3% and 3.5% fat), homogenized fresh milk (3.5% fat), non-homogenized milk 3.8%, 30% UHT-cream or a 3% micellar casein isolates containing preparation were performed, followed by a continued intraoral slab exposure for 8 h overnight. As control, no rinse was adopted. Afterwards, bacterial adhesion was quantified by DAPI staining and bacterial viability was determined by BacLight LIVE/DEAD-staining. Extracellular polysaccharides were visualized by Concanavalin A/Alexa-Fluor 594-staining. Statistical analysis was performed by the Kruskal-Wallis test and the Mann-Whitney U test followed by Bonferroni-Holm correction. Results After 8 h of intraoral biofilm formation, 1.62*106±1.68*106 bacteria/cm2 were quantified in the control samples. Viability staining showed a distribution of 35% vital to 65% avital bacteria. None of the applied mouthrinses showed a significant change (p > 0.01) in bacterial colonization. A tendency to reduce bacterial colonization in situ was observed for non-homogenized milk and casein micelles. Conclusion Mouthrinsing with bovine milk and milk protein isolates had no significant impact on initial biofilm formation at the tooth surface. Clearly, it does not increase bacterial colonization.